Using tax return data to simulate corporate marginal tax rates - Graham, John R.; Mills, Lillian F. (Journal of Accounting and Economics, 2008)
We document that simulated corporate marginal tax rates based on financial statement data [Shevlin, T., 1990. Estimating corporate marginal tax rates with asymmetric tax treatment of gains and losses. The Journal of the American Taxation Association 11, 51–67; Graham, J., 1996a. Debt and the marginal tax rate. Journal of Financial Economics 41, 41–73] are highly correlated with simulated rates based on corporate tax return data. We provide algorithms that can be used to estimate the book or tax simulated rates when they are not available. We find that the simulated book marginal tax rate does a better job of explaining financial statement debt ratios than does the analogous tax return variable and discuss how the book-simulated rate is likely to be an appropriate measure in settings with global, long-term considerations.